Development of 13 microsatellite markers for Castanopsis tribuloides (Fagaceae) using next-generation sequencing - Pimubon Waikham (2018)
© 2017, Springer Science+Business Media B.V., part of Springer Nature. Catanopsis tribuloides is a climax tree species commonly distributed in evergreen forests and has been used to restore degraded areas in northern Thailand. To aid in study of genetic diversity of the species, microsatellite markers, which are specific to C. tribuloides, were developed using whole genome sequencing by next-generation sequencing technology. The primers for microsatellite were developed and screened for optimal annealing temperature by PCR assay. The loci primers specific with C. tribuloides, 13 polymorphic microsatellite primers were successfully developed. The results from genetic information analyzing showed the number of alleles presented were between 2 and 24. Accordingly, the expected and observed heterozygosity obtained were between 0.298 and 0.920 and 0.364 to 1.000, respectively. Null allele frequency was presented 0.000–0.199. Genetic information was generated 10 loci primers significantly deviated from Hardy–Weinberg Equilibrium. All 13 primer pairs of loci were not significant with linkage disequilibrium. A set of microsatellite markers in this study could be applied to gene flow, genetic structure and population genetic studies in the future.